Maxim Analysis of Maxim Usage in Marital Conversations: A Study of Batak Couple Dynamics in the Movie 'Ngeri-Ngeri Sedap’ - Syafrayani, Putri Rizki; Ayunda, Riska (English Teaching and Linguistics Journal (ETLiJ), 2025)
This study analyzed the application and violation of Grice's maxims in marital conversations between Batak couples as depicted in the film